The intrinsic value of decision rights: A note on team vs individual decision-making - Justin Buffat; Matthias Praxmarer; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2020)
Team decision-making prevails in modern organizations. Teams often need to decide whether to delegate or make a decision themselves. Recent work has found that many individuals assign a significantly positive intrinsic value to having a decision right, which may distort the choice between delegating a decision or not. Here we examine experimentally whether teams are also prone to such distortions. While in the aggregate we find no differences between individuals and teams, we uncover an important heterogeneity within teams. Teams with a smooth decision making process have much lower intrinsic values of decision rights than individuals, often not even significantly different from zero. Yet, teams with conflicts in reaching a decision have very high intrinsic values of decision rights, thus distorting decisions. Hence, the team decision making process is of significant importance for the decision-making quality in organizations.
Keywords: C92; D23; D80; 330; Decision rights; intrinsic value; team decision making; experiment